Separate Paths : Lenapes and Colonists in West New Jersey - Soderlund, Jean R., 1947- (Book collections on Project MUSE., 2022)
"Separate Paths: Lenapes and Colonists in West New Jersey is the first cross-cultural study of European colonization in the region south of the Falls of the Delaware River (now Trenton). Lenape men and women welcomed their allies, the Swedes and Finns, to escape more rigid English regimes on the west bank of the Delaware, offering land to establish farms, share resources, and trade. In the 1670s, Quaker men and women challenged this model with strategies to acquire all Lenape territory for their own use and to sell as real estate to new immigrants. Though the Lenapes remained sovereign and "old settlers" retained their Swedish Lutheran religion and ethnic autonomy, the West Jersey proprietors had considerable success in excluding Lenapes from their land. The Friends believed God favored their endeavor with epidemics of smallpox and other European diseases that destroyed Lenape families and communities. Affluent Quakers also introduced enslavement of imported Africans and Natives-and the violence that sustained it-to a colony they had promoted with the liberal West New Jersey Concessions of 1676-77. Thus, they defied their prior experience of religious persecution and their principles of peaceful resolution of conflict, equality of everyone before God, and the golden rule to treat others as you wish to be treated. Despite mutual commitment to peace by Lenapes, old settlers, and Friends, Quaker colonization had similar results to military conquests of Natives by English in Virginia and New England, and Dutch in the Hudson Valley and northern New Jersey. Still, in alliance with old settlers, Lenape communities survived in areas outside the focus of English colonization, in the Pine Barrens, upper reaches of streams, and Atlantic shore"--